Long non-coding RNAs direct the SWI/SNF complex to cell type-specific enhancers - Oo, James A.; Warwick, Timothy; Pálfi, Katalin; Lam, Frederike; McNicoll, François; Prieto García, Cristian; Günther, Stefan; Cao, Can; Zhou, Yinuo; Gavrilov, Alexey A.; Razin, Sergey V.; Cabrera-Orefice, Alfredo; et al. (Nature Communications, 2025)
The coordination of chromatin remodeling is essential for DNA accessibility and gene expression control. The highly conserved and ubiquitously expressed SWItch/Sucrose Non-Fermentable (SWI/SNF) chromatin remodeling complex plays a central role in cell type- and context-dependent gene expression. Despite the absence of a defined DNA recognition motif, SWI/SNF binds lineage specific enhancers genome-wide where it actively maintains open chromatin state. It does so while retaining the ability to respond dynamically to cellular signals. However, the mechanisms that guide SWI/SNF to specific genomic targets have remained elusive. Here we demonstrate that trans-acting long non-coding RNAs (lncRNAs) direct the SWI/SNF complex to cell type-specific enhancers. SWI/SNF preferentially binds lncRNAs and these predominantly bind DNA targets in trans. Together they localize to enhancers, many of which are cell type-specific. Knockdown of SWI/SNF- and enhancer-bound lncRNAs causes the genome-wide redistribution of SWI/SNF away from enhancers and a concomitant differential expression of spatially connected target genes. These lncRNA-SWI/SNF-enhancer networks support an enhancer hub model of SWI/SNF genomic targeting. Our findings reveal that lncRNAs competitively recruit SWI/SNF, providing a specific and dynamic layer of control over chromatin accessibility, and reinforcing their role in mediating enhancer activity and gene expression.
Gesehen am 16.01.2026